Planejamento, implantação e manejo de trilhas ecológicas em fragmentos florestais: uma proposta de uso conservacionista - Moraes, Daniele Inês de (2014)
This research aimed to identify the procedures required for nature trails in forested areas´ deployment and management, considering benefits and problems of its use in small farms. Through literature review and empirical studies, it was possible to survey the methods and techniques of deployment, use and management of trails in forested areas, and to evaluate physical and environmental conditions, the user profile and interpretative activities in two ecological trails located in a small farm open to visitors, called Recanto Renascer, located in the municipality of Francisco Beltrão, state of Parana, Brazil. To assess the impact on the trails, the methodology Monitoring the Impact of the Visitation (IVM) was used. For the analysis of the attractiveness of each track, we used the methodology of Interpretative Attractiveness Index Points (IAPI). Soil analysis for verification of soil compaction on the trails were also done. The results obtained from the research used to develop proposals for physical- environmental and interpretive adequacy of the two tracks of Recanto Renascer, beyond the preparation of a material with technical information to owners of farms interested in establishing nature trails or in adapting existing trails.